Tax Regulatory Reforms and Business Sustainability in the Palm Oil Sector: A Systematic Review - Tandiawan, Vira (Institut Bisnis dan Informatika Kesatuan, 2025)
The palm oil industry is vital to the regional economy but faces significant challenges regarding tax management and compliance with evolving regulations. Despite the Omnibus Law’s aim to simplify Indonesia’s tax system and enhance transparency, its specific impacts on tax management strategies in the palm oil sector remain poorly understood. This study examines the impact of tax regulatory reforms on tax management strategies and business sustainability in the palm oil plantation sector in Central Sulawesi. Through a systematic literature review, this research synthesizes existing studies on tax management, regulatory changes, and sustainability practices in the palm oil industry. The findings highlight that while tax reforms have improved compliance and incentivized sustainable practices, businesses still face challenges in adapting to the frequent regulatory changes and balancing sustainability with financial pressures. Tax incentives for sustainable practices, such as reforestation and carbon emission reduction, have become key motivators for companies to integrate environmental and social responsibility into their operations. However, barriers such as high implementation costs and inconsistent adoption across businesses hinder full compliance. This research contributes to understanding how tax reforms can be leveraged to foster sustainability in the palm oil sector, especially in emerging markets like Indonesia.